Dextran-graft-linear poly(ethylene imine)s for gene delivery: Importance of the linking strategy - Ochrimenko, Sofia; Vollrath, Antje; Tauhardt, Lutz; Kempe, Kristian; Schubert, Stephanie; Schubert, Ulrich S.; Fischer, Dagmar (Carbohydrate Polymers, 2014)
Low molar mass linear poly(ethylene imine)s (lPEI) were grafted onto dextran via different synthesis routes aiming at the elucidation of structure-property relationships of dextran-graft-linear poly(ethylene imine) (dex-g-lPEI) conjugates for gene delivery applications. Beside the molar mass of well-defined lPEIs and the linker unit, also the amount of lPEI in the polymeric vectors was varied. The synthesized dextran modifications were characterized regarding their chemical structure and showed enhanced complexation and stabilization of DNA against enzymatic degradation. The transfection efficiency of dex-g-lPEIs was increased compared to unmodified lPEI and revealed a dependency of the used linking strategy. All complexes of DNA and dex-g-lPEIs were found to be nontoxic, but the synthesis route showed a strong influence on the aggregation of red blood cells. In conclusion, the linking strategy of lPEI to dextran has a significant impact on the physicochemical characteristics of DNA/polymer complexes, the biocompatibility as well as the transfection efficiency. © 2014 Elsevier Ltd.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Biocompatibility; Cationized dextran; Gene delivery; Poly(ethylene imine); Structure-property relationship